Synthesis of β-Enaminonitrile-Linked 8-Methoxy-1H-Benzo[f]Chromene Moieties and Analysis of Their Antitumor Mechanisms - Elgaafary, Menna; Fouda, Ahmed M.; Mohamed, Hany M.; Hamed, Abdelaaty; El-Mawgoud, Heba K. A.; Jin, Lu; Ulrich, Judith; Simmet, Thomas; Syrovets, Tatiana; El-Agrody, Ahmed M. (Frontiers in Chemistry, 2021)
A series of aryl-substituted 3-amino-1-aryl-8-methoxy-1H-benzo[f]chromene-2-carbonitriles (4a–4q) were designed and synthesized via reaction of 6-methoxy-2-naphthol with a mixture of appropriate aromatic aldehydes and malononitrile under microwave conditions. The structures of the novel compounds 4b, 4c, 4f, 4g, 4i, 4l, 4m, and 4o–4q were established according to IR, 1H-NMR, 13C-NMR/13C-NMR-DEPT, and MS. The benzochromene derivative 4c with a single chlorine at the meta position of the phenyl ring and, to a lesser extent, other benzochromenes with monohalogenated phenyl ring (4a, 4c–4f) exhibited the highest cytotoxicity against six human cancer cell lines MDA-MB-231, A549, HeLa, MIA PaCa-2, 5,637, and Hep G2. The mechanisms of the cytotoxic activities of benzochromenes with monohalogenated phenyl ring (4a, 4c–4f) were further analyzed using triple-negative breast cancer cell line MDA-MB-231. Cell cycle analysis showed accumulation of the treated cells in S phase for 4a, 4d–4f, and S-G2/M phases for 4c. In vivo, 4a and 4c–4f inhibited growth, proliferation, and triggered apoptosis in preestablished breast cancer xenografts grown on the chick chorioallantoic membranes while exhibiting low systemic toxicity. Compounds 4a and 4c–4f increased levels of mitochondrial superoxide and decreased mitochondrial membrane potential resulting in initiation of apoptosis as demonstrated by caspase 3/7 activation. In addition, 4c induced general oxidative stress in cancer cells. The SAR study confirmed that halogens of moderate size at meta or para positions of the pendant phenyl ring enhance the cytotoxic activity of 3-amino-1-aryl-8-methoxy-1H-benzo[f]chromene-2-carbonitriles, and these compounds could serve as leads for the development of novel anticancer therapies.